Estudo comparativo sobre a eficácia de duas drogas de ação anti-inflamatória (Etoricoxib e Diclofenaco) após exodontia de terceiros molares inferiores inclusos. - Gabrielli, Marisa Aparecida Cabrini [UNESP]; Vieira, Eduardo Hochuli [UNESP]; Pereira-Filho, Valfrido Antonio [UNESP]; Real Gabrielli, Mário Francisco [UNESP]; Souza, Raphael Freitas de; Primo, Bruno Tochedo; Kluppel, Leandro Eduardo (My University, 2012)
In this article the authors clinically compare the efficacy of two different anti-inflammatory drugs - Etoricoxib (Arcoxia®) and Diclofenac (Olfen®) – in the control of postoperative pain resulting from the surgical removal of impacted lower third molars. Fifteen patients requiring the extraction of bilaterally impacted lower third molars were selected at the Department of Oral and Maxillofacial Surgery at the Araraquara School of Dentistry – UNESP. The drugs were randomly administered during the first and second surgical procedures. Pain was evaluated by means of a visual analogic scale for 72 hours following the surgical procedure. After statistical analysis of the results, the authors concluded that there were no significant differences in terms of postopoerative pain control between the two drugs studied.

Neste trabalho, os autores compararam clinicamente a eficácia de duas drogas de ação anti-inflamatória: o Etoricoxib (Arcoxia®) e Diclofenaco (Olfen®) no controle da dor pós-operatória, na exodontia de terceiros molares inclusos. Foram selecionados 15 pacientes adultos da Disciplina de Cirurgia e Traumatologia Buco-Maxilo-Facial da Faculdade de Odontologia de Araraquara – Unesp que necessitavam de extrações de terceiros molares inferiores bilateralmente. As drogas foram administradas na primeira e na segunda cirurgia aleatoriamente. A dor foi avaliada por meio de escala analógica visual, por 72 horas pós-operatórias. Concluiu-se, após a análise dos resultados, que não houve diferenças estatísticas significantes entre as duas drogas no controle da dor pós-operatória.
Comparative study of the efficacy of two different anti-inflammatory drugs (Etoricoxib and Diclofenac) following removal of impacted lower third molars
Keywords: Pain; Third molars; Anti-inflammatory; Dor; Terceiros molares; Antiinflamatórios